1998
DOI: 10.1038/sj.onc.1202227
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of eukaryotic polypeptide chain initiation factor (eIF) 4G in response to induction of apoptosis in human lymphoma cell lines

Abstract: We have investigated the e ect of inducing apoptosis in BJAB and Jurkat cells on the cellular content of several polypeptide chain initiation factors. Serum deprivation results in inhibition of protein synthesis and induction of apoptosis in BJAB cells; at early times, there is selective degradation of polypeptide initiation factor eIF4G but no major losses of other key initiation factors. The disappearance of full length eIF4G is accompanied by the appearance of smaller forms of the protein, including a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 65 publications
10
154
2
Order By: Relevance
“…38 We also assessed the levels of several other initiation factors in the BJAB cells under the same conditions. Figure 1B shows that, in agreement with our previous results, 34 the levels and integrity of poly(A)-binding protein (PABP), eIF4A and total eIF4E were unaffected in apoptotic cells. However, use of antiserum which was specific for the phosphorylated form of eIF4E 39 indicated that the phosphorylation status of eIF4E decreased at later times following the induction of apoptosis ( Figure 1B, lanes 4 ± 6).…”
Section: Characterisation Of the Cleavage Fragments Of Eif4g In Apoptsupporting
confidence: 80%
See 2 more Smart Citations
“…38 We also assessed the levels of several other initiation factors in the BJAB cells under the same conditions. Figure 1B shows that, in agreement with our previous results, 34 the levels and integrity of poly(A)-binding protein (PABP), eIF4A and total eIF4E were unaffected in apoptotic cells. However, use of antiserum which was specific for the phosphorylated form of eIF4E 39 indicated that the phosphorylation status of eIF4E decreased at later times following the induction of apoptosis ( Figure 1B, lanes 4 ± 6).…”
Section: Characterisation Of the Cleavage Fragments Of Eif4g In Apoptsupporting
confidence: 80%
“…We have reported previously that all of these treatments also result in the complete cleavage of eIF4GI into a series of characteristic fragments. 34 Figure 1B illustrates the time-course of eIF4GI cleavage in response to induction of apoptosis with cycloheximide, as visualised with a number of domain and sequence-specific antisera (W, RL, E; see Materials and Methods and Figure 3). In agreement with our previous data, 34,35 antiserum generated against a large Cterminal fragment of eIF4G (W) showed that cycloheximide induced the cleavage of total cytoplasmic eIF4GI to yield the novel ca.…”
Section: Characterisation Of the Cleavage Fragments Of Eif4g In Apoptmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of eIF4E and p70 S6 kinase is therefore clearly not a consequence of apoptosis. It also precedes the cleavage of 4E-BP1, which we observed in cells treated with any of the DNAdamaging agents used at later times when caspases are active (Figures 1b, 4c, 5a,b), and the cleavage of eIF4G 1 (Figure 2f), which occurs as a consequence of caspase-3 activation in cells which are actively undergoing apoptosis (Clemens et al, 1998;Marissen and Lloyd, 1998;Bushell et al, 1999). The broad-speci®city caspase inhibitor Z-VAD.FMK did not prevent the inhibition of protein synthesis (Figure 6), the inactivation of p70 S6 kinase (Figure 2a), the dephosphorylation of 4E-BP1 (Figure 2c) or the dissociation of eIF4E:eIF4F complexes (data not shown), demonstrating that all these e ects are independent of caspase activity.…”
Section: Discussionmentioning
confidence: 66%
“…This event is thus also independent of caspase activation and the onset of apoptosis. eIF4G 1 has previously been shown to be degraded in cells undergoing apoptosis (Marissen and Lloyd, 1998;Clemens et al, 1998) and this requires caspase activity/ activation (Marissen and Lloyd, 1998;Bushell et al, 1999). We therefore analysed the total level of eIF4G 1 in ) were used in the in vitro p70 S6 kinase activity assay as described in Materials and methods.…”
Section: Effects Of Etoposide On Downstream Targets Of Mtor Signallingmentioning
confidence: 99%